APPLICATION DEVELOPMENT USING POINT OF SALES AGILE METHODS WITH SCRUM PATTERNS - Praba, Ardian Dwi; Santoso, Tri (Sean Institute, 2022)
Many business actors still carry out their business processes manually which has many limitations in the process. Where the transaction process as well as financial calculations and profits still have to be done manually which takes a long time. This is also inseparable from the human error factor that everyone has. With these things in mind, it is appropriate for business actors to find solutions to the problem. One solution that can be done is to design a Point Of Sales application. Where Point Of Sales is an application that is used to manage a transaction so that the transaction process can run quickly, easily and accurately. With this application, business owners can easily see and also monitor transactions that occur in their business so that it will be very helpful in making policies from a company. By adding the use of the Agile method and the Scrum pattern at the Point Of Sales will make the application even better in performance.